Tissue-Specific Factors Differentially Regulate the Expression of Antigen-Processing Enzymes During Dendritic Cell Ontogeny - Mahiddine, Karim; Hassel, Chervin; Murat, Claire; Girard, Maeva; Guerder, Sylvie (Frontiers in Immunology, 2020)
Dendritic cells (DC) form a collection of antigen-presenting cells that are distributed throughout the body. Conventional DC (cDC) which include the cDC1 and cDC2 subsets, and plasmacytoid DC (pDC) constitute the two major ontogenically distinct DC populations. The pDC complete their differentiation in bone-marrow (BM) while the cDC subsets derive from pre-committed bone-marrow (BM) precursors, the pre-cDC, that seed lymphoid and non-lymphoid tissues where they further differentiate into mature cDC1 and cDC2. Within different tissues, cDC express distinct phenotype and function. Notably cDC in the thymus are exquisitely efficient at processing and presenting antigens in the class II pathway, while in the spleen they do so only upon maturation induced by danger signals. To appraise this functional heterogeneity, we examined the regulation of the expression of distinct antigen-processing enzymes during DC ontogeny. We analyzed the expression of cathepsin S (CTSS), cathepsin L (CTSL) and thymus specific serine protease (TSSP), three major antigen-processing enzymes regulating class II presentation in cDC, by DC BM precursors and immature and mature cDC from spleen and thymus. We found that pre-cDC in the BM express relatively high levels of these different proteases. Then, their expression is modulated in a tissue-specific and subset–specific manner with immature and mature thymic cDC expressing overall higher levels than immature splenic cDC. On the other hand, TSSP expression level is selectively down-regulated in spleen pDC while CTSS and CTSL are both increased in thymic and splenic pDC. Hence tissue-specific factors program the expression levels of these different proteases during DC differentiation thus conferring tissue-specific function to the different DC subsets.